ANALISIS EFEKTIVITAS SISTEM PROSEDUR PIUTANG PADA CV PELUMASINDO KALBAR - admin, HADI HARTANTO B41110031 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The application of Internal Control System in companies is intended for their efficiency and effectiveness on their operational activities. The receivables system and procedures are supposed to be effective so it would not inflict any loss to the companies. This research is intended to find out about the applied receivables system and procedures in CV Pelumasindo Kalbar, and to find out the control that affecting the receivables system and procedures’ effectiveness in CV Pelumasindo Kalbar. This research is a descriptive one, with case study method. The required data in this research are collected from organization structure analysis, flowchart, internal control questionnaire, compliance test, and documentary study. The results showed that the applied receivables system and procedures in CV Pelumasindo Kalbar are adequate according to the results of compliance test and internal control questionnaire; and the questionnaires’ results in 82.5%, which shown that the applied receivables system and procedures in CV Pelumasindo Kalbar is effective. Keywords: system, procedures, internal control, receivables, compliance test